Parental Factors Associated With Internet Gaming Disorder Among First-Year High School Students: Longitudinal Study - Rui She; Youmin Zhang; Xue Yang (JMIR Publications, 2022)
BackgroundParents play central roles in adolescents' socialization, behavioral development, and health, including the development of internet gaming disorder (IGD). However, longitudinal research on the parental predictors of adolescent IGD is limited. ObjectiveThis study aimed to investigate the reciprocal associations between various parental factors and adolescent IGD using 2-wave cross-lagged models. MethodsA sample of 1200 year-one high school students in central China completed a baseline assessment in 2018 (mean age 15.6 years; 633/1200, 52.8% male) and a follow-up survey in 2019. IGD was measured using the 9-item DSM-5 IGD Symptoms checklist. Perceptions related to parental variables, including psychological control, parental abuse, parental support, and the parent-child relationship, were also collected from the adolescents. ResultsOf all the participants, 12.4% (148/1200) and 11.7% (140/1200) were classified as having IGD at baseline (T1) and follow-up (T2), respectively. All 4 cross-lagged models fit the data well (range for the comparative fit index .91-.95; range for the standardized root mean square residual .05-.06). Parental support (β=-.06, P=.02) and parental abuse (β=.08, P=.002) at T1 predicted IGD symptoms at T2, while parental psychological control (β=.03, P=.25) and a positive relationship with parents (β=-.05, P=.07) at T1 had nonsignificant effects on IGD symptoms at T2, when controlling for background variables. In addition, IGD symptoms at T1 did not predict parental factors at T2. ConclusionsThe findings suggest that parental factors may be significant predictors of adolescent IGD. Health interventions should consider involving parents to increase the effectiveness of treatment to prevent and reduce adolescent IGD.